Neutrophil extracellular traps are increased in patients with acute ischemic stroke: prognostic significance - Vallés, Juana; Lago, Aida; Santos, María Teresa; Latorre, Ana María; Tembl, José I.; Salom, Juan B.; Nieves, Candela; Moscardó, Antonio (Thrombosis and Haemostasis, 2017)
Neutrophil extracellular traps (NETs) are networks of DNA, histones, and proteolytic enzymes produced by activated neutrophils through different mechanisms. NET formation is promoted by activated platelets and can in turn activate platelets, thus favoring thrombotic processes. NETs have been detected in venous and arterial thrombosis, but data in stroke are scarce. The aim of this study was to evaluate NETs in the plasma of patients with acute ischemic stroke and their potential association with baseline clinical characteristics, stroke severity, and one-year clinical outcomes. The study included 243 patients with acute ischemic stroke. Clinical and demographic data and scores of stroke severity (NIHSS and mRs) at onset and discharge were recorded. Markers of NETs (cell-free DNA, nucleosomes, and citrullinated histone 3 (citH3)), were determined in plasma. Patients were followed-up for 12 months after the ischemic event. NETs were significantly elevated in the plasma of patients with acute ischemic stroke when compared to healthy subjects. NETs were increased in patients who were over 65 years of age and in those with a history of atrial fibrillation (AF), cardioembolic stroke, high glucose levels, and severe stroke scores at admission and discharge. In multivariate analysis, elevated levels of citH3, the most specific marker of NETs, at onset were independently associated with AF and all-cause mortality at oneyear follow-up. NETs play a role in the pathophysiology of stroke and are associated with severity and mortality. In conclusion, citH3 may constitute a useful prognostic marker and therapeutic target in patients with acute stroke.
Keywords: Stroke; extracellular traps; atrial fibrillation; glucose; immunity